2020
DOI: 10.3390/su12219230
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Mechanical Properties of Concrete Incorporating Aluminum Dross, Fly Ash, and Quarry Dust

Abstract: The amount of waste, associated waste disposal costs, and environmental contamination may be minimized by identifying effective recycling approaches. These promising approaches will also lead to the protection of natural resources and economic gains. One example of waste disposal maybe by using it as a filling material or as a pozzolanic material for the production of concrete. In this regard, this study proposes to partially replace cement with aluminum dross and fly ash, and partially replace natural sand wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This can be attributed to the angular shape and texture of CSD compared to river sand. Cheah et al [ 68 ] observed significant reduction in workability of concrete by incorporating 60% quarry dust due to insufficient compaction of concrete mix containing rough and porous quarry dust aggregates [ 69 ]. Likewise, incorporation of NF reduces the workability of concrete since the presence of fiber decreases the fluidity of the concrete mix [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the angular shape and texture of CSD compared to river sand. Cheah et al [ 68 ] observed significant reduction in workability of concrete by incorporating 60% quarry dust due to insufficient compaction of concrete mix containing rough and porous quarry dust aggregates [ 69 ]. Likewise, incorporation of NF reduces the workability of concrete since the presence of fiber decreases the fluidity of the concrete mix [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aluminum dross is a waste ash generated during aluminum production, which comes from infusible inclusions [1], oxides, and various additives that float on the aluminum melt surface during smelting [2]. As a typical solid waste product from the aluminum processing industry, it has been included in China's "National Hazardous Waste List (2021 edition)" due to its reactivity and leaching toxicity [3].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of AD mainly includes Al, AlN, Si, SiO 2 , MgAlO 4 and other salts. Aluminum is the most abundant metallic element in the Earth's crust and has an excellent combination of chemical, mechanical and physical properties, which makes it suitable for many applications, such as cement, refractory matter, polyaluminum chloride (PAC), ceramics, concrete, geomaterial and alloys [2][3][4]. AD is mainly disposed of by landfill, and Waste 2022, 1…”
Section: Introductionmentioning
confidence: 99%